Lead Removal Through The Adsorptions Of Reactivated Carbon - Ahmad, Muhammad Hamizan (Universiti Sains Malaysia, 2022)
In this study, performance of heavy metal removal using reactivated carbon and best parameters in order to remove the heavy metal using different parameters applied has been successfully investigated. Spent Reactivated Carbon (SAC) has been efficiently regenerated by combining chemical and thermal reactivation together. It was done in water bath at 85° C with the Sodium Hydroxide (NaOH) as the regenerant. Afterward, the Reactivated Carbon (RAC) undergone thermal reactivation by heating in furnace for 4 hours at 400°C. Prior and after reactivation, the SAC were undergone pretreatment process such as pre washed and post washed. Then, the RAC obtained has been used in the adsorption of heavy metal (lead, Pb) in batch. Different parameters have been incorporated to in order to obtained the optimized adsorption process for Pb removal. The results show that, increase in pH around pH 4 to 6 has the highest percent of Pb removal. The mass of RAC used at 3 g shows and optimum removal percentage. The initial concentration also shows that 100 ppm has the highest percentage of removal at 3 g of RAC used. Last but not least, contact time at 2 hours shows the highest removal percentage of Pb ions.